2020
DOI: 10.1038/s41598-020-70586-x
|View full text |Cite
|
Sign up to set email alerts
|

Mineral nitrogen captured in field-aged biochar is plant-available

Abstract: Biochar may serve as a tool to sustainably mitigate climate change via carbon sequestration and by improving soil fertility. Biochar has shown to retain nitrate in its pores, which increases with an organic coating of the inner surfaces and residence time in soil ("aging"). Here we investigated the plant accessibility of the captured nitrate in field-aged biochar, as a prerequisite for developing carbon-based N fertilization techniques with environmental benefits. Based on previous results, we hypothesized tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 47 publications
(85 reference statements)
2
32
0
Order By: Relevance
“…SW500, however, significantly inhibited the flow of nitrate, despite not exhibiting chemical affinity in sorption trials. This suggests the physical retention mechanism known as nitrate capture, which is believed to be facilitated by increased surface area and porosity (Haider et al, 2016(Haider et al, , 2020Kameyama et al, 2012;Kammann et al, 2015). Indeed, SW500 had a substantially larger surface area than AS500 (93.5 compared to 54.7 m 2 g -1 ).…”
Section: Column Experiment-nutrient Retentionmentioning
confidence: 99%
See 2 more Smart Citations
“…SW500, however, significantly inhibited the flow of nitrate, despite not exhibiting chemical affinity in sorption trials. This suggests the physical retention mechanism known as nitrate capture, which is believed to be facilitated by increased surface area and porosity (Haider et al, 2016(Haider et al, , 2020Kameyama et al, 2012;Kammann et al, 2015). Indeed, SW500 had a substantially larger surface area than AS500 (93.5 compared to 54.7 m 2 g -1 ).…”
Section: Column Experiment-nutrient Retentionmentioning
confidence: 99%
“…Despite increased interest and investigation, there remains uncertainty regarding the ability of biochar to deliver these agronomic benefits. While many studies show promising results where nutrient retention and soil water dynamics are concerned (Blanco-Canqui, 2017;Glaser et al, 2002Glaser et al, , 2015Glaser and Lehr, 2019;Haider et al, 2020;Hestrin et al, 2019), others have demonstrated no or only minor effects (Griffin et al, 2017;Jones et al, 2012;Martos et al, 2020). Several authors have concluded that, due to differences in biochar production parameters and those of the soil environment, material and site-specific investigation is required before conclusions can be drawn about the potential of biochar to provide agricultural benefits (Hassan et al, 2020;Jeffery et al, 2011;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the report by 51 , there is a signi cant increasing in the N content after the applications of different organic amendments such as dairy cattle manure, fresh white clover, vegetable, fruit, and yard waste compost, and poplar tree compost as a result of mineralization of organic nitrogen in the organic amendments. Some studies also reported that reduced N (nitrate) leaching when biochar was applied to soil combined with mineral or organic N fertilizer 52 . Our results also showed that soil residual available P content was increased in the control compost, 5% co-composted biochar, 15% co-composted biochar, 25% co-composted biochar, khat biochar and 50% NPF + compost by 3.1% − 12.7%, while in the 100% NPF and control soil residual available P reduced by 6.2% and 2.8% respectively compared to the value before harvesting.…”
Section: Effects Of Amendments On Soil Residual Physicochemical Propertiesmentioning
confidence: 99%
“…Biochar has been proposed as a soil amendment to enhance nutrient retention, reduce nutrient losses, improve soil fertility and crop growth, and sequestrate carbon [ 7 , 8 ]. In some cropping systems, biochar addition helps to reduce nitrogen fertiliser input while maintaining productivity [ 9 ] as biochar serves as a good complement to site preparation techniques that are frequently used for capturing nitrogen from nitrate so as to increase rhizosphere nitrogen bioavailability in alkaline soils [ 10 ]. According to other reports, biochar application level influences soil nutrient and plant root phenotype [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%